The Effect of Understanding Arabic Language Rules on the Process of Memorizing the Qur'an: A Case Study at MIT Sahabat Quran Anas Bin Malik - Ulfah Mardliyah Husnayain,; Budi Harjo, (Shaut al Arabiyyah, 2025)
This study aims to determine the extent to which understanding of Arabic language rules affects the process of memorizing the Qur'an in MIT Sahabat Quran Anas Bin Malik students. The method used is a qualitative approach with the type of case study. Data collection techniques were conducted through in-depth interviews, direct observation, and documentation. The results showed that students who have a basic understanding of nahwu rules tend to be easier in memorizing, especially in understanding the structure of sentences and the meaning of verses. The tahfidz teachers and Arabic language teachers both stated that the integration between Arabic language learning and tahfidz can improve the accuracy and retention of students' memorization. However, the level of influence varies depending on students' learning styles, motivation and readiness. This study concludes that the understanding of Arabic language rules contributes significantly to the quality of memorization of the Qur'an if applied contextually and integratively. This finding can serve as a basis in designing more meaningful and sustainable memorization learning methods at the primary madrasah level.